Correlations Between Anti-SARS-CoV-2 Titers, CD4+ T-Cell Counts, and COVID-19 Severity - Edwin Hadinata; Eko Surachmanto; Paul N. Harijanto (Biology, Medicine, & Natural Product Chemistry, 2026)
Coronavirus disease 2019 (COVID-19) presents with diverse symptoms ranging from mild to severe. Patients with severe COVID-19 can show impaired humoral and cellular immunity and excessive pro-inflammatory cytokine production. Antibodies are generated against severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) due to the activation of the humoral immune system. Molecular-based testing is currently used to diagnose COVID-19. Determining antibody and CD4+ T cell counts can help monitor the antibody response to assess the risk of reinfection and vaccine response. This study aimed to determine the relationships between Aanti-SARS-CoV-2 titer, CD4+ T cell count, and COVID-19 severity. This analytic observational study used a cross-sectional design with consecutive sampling and was conducted at RSUP Prof. Dr. R. D. Kandou Manado Hospital from April to October 2021. It comprised 48 patients with COVID-19. The data were compared using Spearman’s rank correlation coefficient (rs). Anti-SARS-CoV-2 titers were nonsignificantly correlated with COVID-19 severity (rs = 0.081, p = 0.582) and CD4+ T cell counts (rs = 0.214, p = 0.145). In contrast, CD4+ T cell counts were significantly negatively correlated with COVID-19 severity (rs = -0.454, p = 0.001). Anti-SARS-Cov-2 titers cannot be used as an indicator of COVID-19 severity. Moreover, CD4+ T cell counts cannot be used as a marker of anti-SARS-CoV-2 titers. However, COVID-19 severity correlates negatively with CD4+ T cell counts, indicating that CD4+ T cell counts can be used as an indicator of COVID-19 severity.